Analysis Study of Survey for Safety and Efficacy of Pharmacopuncture - Hong Kwon-eui (Korean Pharmacopuncture Institute, 2010)
This study was done in order to present clinical trial method for safety and efficacy of Pharmacopuncture. The results were summarized as follow:Objective : The purpose of this study is to verify about safety and effectiveness of pharmacopuncture. Methods : We use questionnaire created by expert group. Survey was conducted to target clinicians who using pharmacopuncture more then 5 years. Results & Conclusion : Pharmacopuncture is effective. and that is widely used in the musculoskeletal diseases. but treatment method has not been organized to objectivity. Some pharmacopuncture causes specific symptoms, but no serious side effects. Generally, pharmacopuncture is effective and safety. * This study is performed under the Research and Development Project of Korean Pharmacopuncture Institiute(2010)'s sponsorship.